IMPLEMENTATION OF WATERFALL METHOD IN PD INVENTORY INFORMATION SYSTEMADIWANGI KARAWANG - fitri isnaini; Wahyudi Prabowo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
In the era of Information Systems, development changes, especially in the field of sales, have changed very rapidly. AdiWangi Trading Company is one of the companies engaged in the sale of staple goods. In providing services to customers and the general public, PD Adiwangi has not been able to fulfill information needs optimally. The process of data collection is still done manually, so it takes a long time to complete it. With the current process, customers often feel that they have been served a long time and for the company itself there are often differences between the items in the data recorded and the items stored in PD Adiwangi, so that why this research uses waterfall method. The design stages used include program planning, program design, database, and program development. Inventory Information System with manual record by inputting into excel and record incoming goods. Whereas, outcoming goods recorded rarely, employees are not taken for placement on shelves. It has become a habit until now so that inventory of goods also not observed. From the results of the study, it can be concluded that the program design made named Inventory program design at PD AdiWangi. It is expected to facilitate the process of data collection, as well as making reports quickly and accurately compared to systems manually.